2010
DOI: 10.2967/jnumed.110.077578
|View full text |Cite
|
Sign up to set email alerts
|

The α-Camera: A Quantitative Digital Autoradiography Technique Using a Charge-Coupled Device for Ex Vivo High-Resolution Bioimaging of α-Particles

Abstract: Bioconjugates used in internal radiotherapy exhibit heterogeneous distributions in organs and tumors, implying a risk of nonuniform dose distribution in therapeutic applications using a-particle emitters. Tools are required that provide data on the activity distribution for estimation of absorbed dose on a suborgan level. The a-camera is a quantitative imaging technique developed to detect a-particles in tissues ex vivo. The aim of this study was to evaluate the characteristics of this imaging system and to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 17 publications
1
79
0
Order By: Relevance
“…27 Cryosections of spleen and femur from leukemia-bearing mice treated with 211 At-B10-30F11 were imaged with the a-camera technique at various time points after radiolabeled injections. At the 3-hour time point, a-camera imaging revealed that 211 At was distributed throughout the spleen and bone marrow, with some variability that correlates with suborgan architecture.…”
mentioning
confidence: 99%
“…27 Cryosections of spleen and femur from leukemia-bearing mice treated with 211 At-B10-30F11 were imaged with the a-camera technique at various time points after radiolabeled injections. At the 3-hour time point, a-camera imaging revealed that 211 At was distributed throughout the spleen and bone marrow, with some variability that correlates with suborgan architecture.…”
mentioning
confidence: 99%
“…Repeated sampling of peritoneal fluid has also been reported ). In principle, measurements or images of biopsies from organs of interest would be valuable (Bäck et al, 2010), but the increased dosimetric accuracy gained must be weighed against the discomfort such invasive procedures cause the patient. Simple, non-invasive methods using uptake probes can also provide important information on the pharmacokinetics for an individual www.intechopen.com patient.…”
Section: Radiation Dosimetry In the Clinical Situationmentioning
confidence: 99%
“…The a-camera system consisted of a cooled, high-sensitivity charge-coupled device (SXV-H9; Starlight Xpress Ltd.), coupled to a photographic lens (60 mm f/2.8 Micro-Nikkor; Nikon Corp.) (12). Specimens to be imaged (i.e., tissue sections on a scintillating sheet) were placed on an adjustable stand below the photographic lens.…”
Section: A-camera Imagesmentioning
confidence: 99%
“…The excised biologic samples were snap-frozen and cryosectioned as previously described (12). Ten to 20 pairs of consecutive sections were analyzed for each sample: one section for a-camera imaging and the other section for staining with hematoxylin and eosin (H&E) (in some cases, 3 consecutive sections were analyzed [ Fig.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation